Analysis Of The Effect Of Care Class On BPJS Claim Values For Patients With The Same Diagnosis At Dustira Class II Hospital - Wulandari, Elmaniar; Wahab, Syaikhul (Jurnal Kesmas Prima Indonesia, 2026)
The National Health Insurance (JKN) program managed by BPJS Kesehatan implements the Indonesia Case-Based Groups (INA-CBGs) prospective payment system. Although INA-CBGs rates are determined based on diagnosis, the treatment class factor has the potential to influence the amount of claims paid. This study aims to analyze the effect of treatment class on the value of INA-CBGs claims in patients with chronic obstructive pulmonary disease (COPD, code J44.1) at Dustira Class II Hospital. This study used an observational analytical design with a cross-sectional approach. The sample consisted of all COPD patients treated at the Kenanga Ward in January 2025 (n=37), with a distribution of Class 1 (n=2), Class 2 (n=13), and Class 3 (n=22). Data analysis was performed using the Kruskal–Wallis test, followed by the Dunn–Bonferroni post-hoc test. The results showed that the highest median claim value was found in Class 1 (Rp 5,264,600), followed by Class 2 (Rp 4,611,500), and Class 3 (Rp 3,958,400). The Kruskal–Wallis test showed a significant difference (H=33.720; p<0.001). Post-hoc analysis showed a significant difference between Class 1 and Class 3 and between Class 2 and Class 3, while the difference between Class 1 and Class 2 was not significant. It was concluded that the treatment class significantly influenced the BPJS claim value in COPD patients. These findings have implications for the evaluation of INA-CBGs tariffs and the preparation for the implementation of the Standard Inpatient Class Policy (KRIS) in 2025.